Trust, control and knowledge transfer in small business networks - Massaro, Maurizio; Moro, Andrea; Aschauer, Ewald; Fink, Matthias (Springer, 2017)
The ability to transfer knowledge effectively in the networks of small and medium-sized firms (SMEs) is paramount for supporting firm competitiveness. Our research is the first one that explores the joint effect of trust and control mechanisms on knowledge transfer in the case of networks of SMEs. We use a multiple case study approach based on six Italian networks of SMEs. We analyse the joint impact of different ethical based trustworthiness factors—namely benevolence and integrity—and the levers of control (LOCs)—namely, belief, boundary, diagnostic and interactive LOCs—on knowledge transfer between SMEs in networks. We find that trust substitutes for the implementation of boundary, diagnostic, and belief tools, while it works jointly with interactive tools in order to support knowledge transfer. These insights not only provide a rich foundation for follow-up research, but also inform SME managers about how to increase the effectiveness and efficiency of knowledge transfer with their network partners.
Keywords: Knowledge transfer; Levers of control; Trust; SME network